PELATIHAN MENINGKATKAN KINERJA SDM PASCA COVID-19 BAGI SISWA SEKOLAH KEWIRAUSAHAAN BINA AMANAH CORDOVA, DI TANGERANG - Aseanty, Deasy; Puspa, Tiara; Matusin, Ina Oktaviana (Jurnal Pengabdian Dharma Bakti, 2021)
The COVID19 pandemic has shocked the world, including in Indonesia. This pandemic has an impact not only on the health sector, with many people exposed and even dying, but also in other sectors, one of which is the economic sector. Low economic growth, in fact there was a recession with a negative growth rate, many companies had to close, workers were laid off, people's incomes tended to decline, and many other changes. The government is also actively involved in regulating this, such as implementing Large Scale Social Restrictions (PSBB), implementing social distancing, even for workers, students and university students, so activities are carried out from home. The impact of all these things has made the Indonesian people more creative in carrying out their daily lives and activities. Including company managers or entrepreneurs or business people, it is necessary to restructure their operational activities and business management. Indonesia needs human resources who are more skilled, more creative, and more able to improve competence and performance than what was done before this panddmi. Thus, each company is expected to be able to manage its business more competitively, both large and SME businesses. The Bina Amanah Cordova School of Entrepreneurship, Tangerang, is one that has also felt the impact of this pandemic. This school is a school dedicated to developing aspiring entrepreneurs. This school produces prospective business people who later they can help the government in increasing its contribution to the economic sector. realize that there is a need for their students and alumni who are already in the SME business to develop the further knowledge and skills needed to manage the challenges faced by any business due to the Covid-19 outbreak. Many students and alumni who are already business people are very aware of this changing situation. They need information, knowledge, related to how to maintain their business in this pandemic era, especially how to increase the competence of business people so that their performance can also increase and this is an effort to maintain the business they run.The Faculty of Economics and Business, Trisakti University through its community service program strives to facilitate the needs faced by students and alumni of the Cordova School of Entrepreneurship. The FEB Usakti Community Service Team (PKM) has conducted training to improve the performance of human resources to remain competitive in a sustainable manner in facing business challenges due to Covid-19, for students and alumni of the Bina Amanah Cordova School of Entrepreneurship, Tangerang. The results of the training evaluation show that students and alumni have been able to significantly improve their performance in increasing competence, especially in terms of how to improve the skills and knowledge needed to survive in running their business (MSME sector), so it can be concluded that the training provided has successfully fulfilled its objectives. .Keywords: Â Covid-19 epidemic, competence, performance, UMKM